Contribuiqáo ao estudo da Passalidofauna (Coleoptera, Scarabaeoidea, Passalidae) em uma área de terra firme da Amazonia Central - Romero Carvalho Mouzinho, José; V. da Fonseca, Claudio Ruy (Instituto de Ecología, A.C., 1998)
Passalidae were studiad during 13 months from October 1992 to October 1993, in 190 ha of upland rainforest near the Solimões river, Manacapuru, Amazonas, Brazil. Nine species belonging to 4 genera were collected; Passalus abortivus, P. epiphanoides, P. interraptus, P. glaberrímus, Popilius marginatas. Veturíus transversus, V. paraensis, Spasalas crenatus and S. elianae. P. abortivus and P. epiphanoides were the most abundant. These coleóptera malnly colonizo fallen trunks in advanced stages of decomposition in thrae different environments: pasture with and without water interference and second growth. In a same trunk up to three different species: P. marginatus, P. epiphanoides e V. transversus were coilected. P. abortivus and P. epiphanoides were found on larger distances intervals from the forest; 420 m and 450 m respectiveiy dístributed in the disturbad area.